Are we observing an NSC in course of formation in the NGC 4654 galaxy? - Schiavi, Riccardo; Capuzzo-Dolcetta, Roberto; Georgiev, Iskren Y.; Arca Sedda, Manuel; Mastrobuono-Battisti, A. (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. We use direct N-body simulations to explore some possible scenarios for the future evolution of two massive clusters observed towards the centre of NG
Gesehen am 09.07.2021